Política sociais e desenvolvimento: o caso de Sinop/MT - Vieira Júnior, Hélio (2020)
The objective of our research was, in general, to understand the relationship between social policies and the development process in the period comprised by Lula’s second Government (2007-2010) and Dilma’s Government (2011-2014), as well as, the impact of this policies on the extension of constitutional social rights. To this end, we propose to study this double and mutually determining process from, on one hand, the analysis of the meaning of social policies of the city of Sinop development process, in the period between the years 2007 and 2014; and, on the other hand, the character verification of these social policies implemented in the city in that period, if it showed more a demercantilization character (in the sense of sharing wealth) or mercantilization (that is, converging to market forces). Considering it is a relatively new municipality and is located in a region of recent colonization, Sinop had, at the end of 2005, a high level of lack on basic infrastructure in several areas, particularly in the areas related to Health, Education, Housing and basic Sanitation. Such index of shortage in basic infrastructure placed the municipality of Sinop as one of the ones that most demanded investments (both in the state and in the midwest region in general), which, among other factors, favored the municipality to be contemplated, since 2006, with the implementation of a set of public policies belonging to the Federal Government's Growth Acceleration Program (PAC), destined for the construction and or expansion of social infrastructure. In this sense, the city of Sinop has placed itself as a privileged space for observing the impact of these policies on the promotion of economic development and the social inclusion process. To the fulfillment of our study, we used, as methodological instruments, bibliographic research, historical research, documentary research and interviews. The implementation, in Sinop, of some of those policies, especifically, in areas such as Health and Education, ended up printing significant changes in the municipality, both from a qualitative and quantitative point of view. The analysis of such impacts, based on Sinop, allow us to observe some significant aspects when development policies prioritize the social.